A pharmacoeconomic study of different brands of commonly prescribed antihypertensive drugs - Upasani, Pooja C.; Barve, Rohidas M.; Hiray, Rajesh S. (International Journal of Basic & Clinical Pharmacology, 2021)
Background: The hypertension is the most common chronic disease, therefore treatment should be affordable. The antihypertensive drugs of same strength are available in market at different costs. This study was undertaken to create awareness among health care workers and patients, about cost difference among different brands of same antihypertensive drug. So that whenever possible, a cheaper effective brand can be prescribed to ensure better patient adherence. Methods: Maximum retail price (MRP) of various antihypertensive drugs of same strength, manufactured by different pharmaceutical companies was obtained from various offline and online sources. The minimum and maximum cost of 10 tablets/capsules noted. The cost ratio and percentage cost variation was calculated for single drug and fixed dose combinations. The ceiling price (as per DPCO) of essential antihypertensives (as per national list of essential medicines) was compared with their maximum cost. Results: The formulations of single antihypertensive drugs (41) and fixed dose combinations of two drugs (19) and three drugs (9) were included in the study. Among the single antihypertensives analyzed the highest cost difference was of eplerenone (50 mg) and high cost ratio and cost variation percentage was of amlodipine (5 mg). Among fixed dose combination of two drugs analyzed highest cost difference was found that of hydrochlorothazide (12.5 mg)+olmesartan (40 mg) combination and highest cost ratio and percentage cost variation was of amlodipine (5 mg)+telmisartan (40 mg). Conclusions: There was a huge price variation among the antihypertensive drugs manufactured by various companies. Some measures must be taken by the government to bring the uniformity in the price that will help to reduce the economic burden on the patients.